The Role of Mentor Teachers in Non-Academic Guidance: Case Study of Senior High School Teaching Assistance Program - Ruswinarsih, Sigit; Widaty, Cucu; P, Reski; Nur, Rahmat; Hidayat Putra, Muhammad Adhitya; Arofah, Lumban; Salsabila Nadhifa , Ramadhanti; Eliza Ramadhani, Novia (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to examine the role of the supervising teacher in non-academic guidance in the Teaching Assistance Program in Senior High Schools. As with technical guidance in the learning process of prospective teachers, non-academic aspects are no less important in the success of the teaching assistance program, but there are still few studies that reveal these aspects. Method: The study was conducted using a qualitative method with data collection through in-depth interviews with supervising teachers and prospective teachers. Results: The results of the study indicate that supervising teachers play a significant role in the development of interpersonal skills, professional ethics, guidance on school environment adaptation, leadership character, and stress management needed by prospective teachers. This non-academic guidance has improved the professional readiness of students, preparing them to face educational challenges. However, there are challenges in implementing this guidance, namely limited time and workload of supervising teachers. This study recommends training for supervising teachers in non-academic guidance aspects and the need for institutional support to improve the effectiveness of the teaching assistance program. Novelty: These findings emphasize the importance of a holistic approach in the education of prospective teachers, which focuses on academic aspects and the development of social and emotional skills.